C.F.G. Gunter as opvoedkundige : 'n studie in die fundamentele opvoedkunde - Steyn, J. C.(Johann Christo),1941- (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (D. Ed.) -- Universiteit van Stellenbosch, 1980.